Develop the Business Intelligence Based on knowledge Management Approach: Case Study of Telecom Operators in Algeria - Boudiaf , Ilyes (Finance and Business Economies Review, 2022)
We aim through this study mainly to measure the impact of knowledge management on Business intelligence through its factors. We have followed descriptive, inductive and experimental approaches. Where we have developed a model that shows the relationship between the variables and its impact (Knowledge management and Business intelligence). In this study we relied on structural dimensions as Leadership, cultivation; Technology, and process. This study was conducted on a sample of 153 individuals from 33 telecom agencies or commercial spaces in Algeria (8 WTA, 11 OTA, 14 AT), where the main results of this study showed the existence of a (strong - positive) correlation and effectiveness of Knowledge management and the Business intelligence.